2019
DOI: 10.1111/josh.12806
|View full text |Cite
|
Sign up to set email alerts
|

Equipping School Health Personnel for Diabetes Care with a Competency Framework and Pilot Education Program

Abstract: BACKGROUND Schools struggle to support health needs of students with diabetes due to limited funding/resources. A competency framework can help individual schools clarify the knowledge and skills required for school‐based diabetes care within their unique context, and inform the development of standardized diabetes education for health staff. METHODS A consensus‐building technique, known as the Delphi method, was used to create a competency framework for diabetes care at school with a panel of 37 stakeholders.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Existing tools have been used to assess diabetes knowledge in school nurses only. 21 With the DDCS, confidence can be measured in tandem with diabetes knowledge to provide different, yet related, information. For example, though a school nurse may have been taught about a certain device, they may not feel confident to use it until they gain additional experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing tools have been used to assess diabetes knowledge in school nurses only. 21 With the DDCS, confidence can be measured in tandem with diabetes knowledge to provide different, yet related, information. For example, though a school nurse may have been taught about a certain device, they may not feel confident to use it until they gain additional experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Readiness to work with diabetes devices includes knowledge, confidence, and the preparatory steps, such as access to and completion of training and supportive school policies for technology use. Existing tools have been used to assess diabetes knowledge in school nurses only 21 . With the DDCS, confidence can be measured in tandem with diabetes knowledge to provide different, yet related, information.…”
Section: Discussionmentioning
confidence: 99%
“…The level of diabetes knowledge increased by 3.5% ( p = 0.01), and the sense of self-efficacy improved by 2.7% ( p = 0.007). Researchers found that developing the competencies of school medical personnel through intensive training and the practical use of specialist knowledge can help organize and provide the best diabetes care in an educational institution [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…We theorized that diabetes knowledge may be a related construct. To assess for convergent validity between device confdence and diabetes knowledge, we coadministered the diabetes knowledge test 2 (DKT2), a validated, multiple-choice test of diabetes knowledge which had previously been adapted for school personnel [18][19][20].…”
Section: Questionnairesmentioning
confidence: 99%